”Sociobiome”: How do socioeconomic factors influence gut microbiota and enhance pathology susceptibility? - A mini-review - Nobre, José Guilherme; Alpuim Costa, D. (Frontiers in Gastroenterology, 2022)
The gut microbiota is becoming well recognized as a key determinant of health and disease. As a result, several studies have focused on causality and the predictive/prognostic value of the microbiota in a wide range of diseases. However, it is of greater importance to understand what sparks changes in the microbiota and how these alterations contribute to an increased susceptibility to disease. A few studies have already demonstrated that the gut microbiota could be modified by lifestyle, consequently leading to pathology. What if socioeconomic factors can also impact the gut microbiota composition and, thus, increase the susceptibility to disease? Perhaps, this is one of the factors that may have contributed to the increased inequalities between people with higher and lower socioeconomic status in terms of health. In this review, we aimed to understand more about this topic and the real impact of the “sociobiome.” Furthermore, we proposed measures to mitigate the impact of these factors on the gut microbiota composition.